THE JAVA CALENDAR AND ITS RELEVANCE WITH THE ISLAMIC CALENDAR - Faiz Farichah (Fakultas Syari'ah dan Hukum UIN Walisongo, 2020)
Calendar or calendar system is an important reference for mankind from ancient times to the present. Judging from the reference system, there are three types of calendars, namely solar-based, lunar-based and both-based calendars. Meanwhile, in terms of its complexity, the calendar is divided into two, namely the astronomical and arithmetic calendars. The Javanese calendar after the changes made by the great sultan, was inspired by the hijri calendar. Both are based on the lunar calendar. The aim of this study is to introduce the calendar system, the Javanese calendar and its relevance to the hijriah calendar, and the Javanese Aboge calendar. This research is descriptive. The source in this research study is literature review. From this research it was found that the hijri calendar is an astronomical calendar that requires observation and has a high degree of accuracy with respect to the visibility of the new moon, while the Javanese calendar is an arithmetic calendar system, so it requires corrections in a certain period to be the same or nearly the same as the hijri calendar. However, the Aboge calendar does not change curves or cycles, so that the Aboge Javanese calendar has a difference of days with the Javanese calendar currently in use, namely the calendar with the asapon calendar, and it could be the same or the difference of up to two days with the Hijri calendar. Yet the calendar is used by the Javanese not only for worship, but also for petungan in determining traditional ceremonies and personal interests.